Profil Pemecahan Masalah Siswa dalam Menyelesaikan Soal Cerita Perbandingan Senilai dan Berbalik Nilai Ditinjau dari Gender pada Siswa Kelas VIII MTS.N 1 Poso Kota - Ahmad TaufiK Aditya; Mustamin Idris; Pathuddin; Alfisyahra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Mathematics plays an important role in daily life, but students often have trouble solving word problems, especially on the topic of direct proportion. This difficulty highlights the need for a profile of students' problem-solving processes to help teachers identify where learning challenges occur. This study aims to describe the problem-solving profile for direct proportion based on the logical-mathematical intelligence of eighth-grade students at SMPN 19 Palu. The research used a descriptive qualitative approach. The subjects of the study were two eighth-grade students chosen based on the results of logical-mathematical intelligence questionnaire, each representing the high (AST) and low (PTR) categories. Data was collected through written tests and in-depth interviews, then analyzed using techniques of data condensation, data presentation, and drawing conclusions. The research results show that AST was able to complete all four stages of Polya completely and accurately with the correct answer (12 liters), while PTR only managed to understand the problem stage and made fundamental conceptual mistakes in the next stages (wrong answer: 5.333 liters). PTR also couldn't verify the answer. It was concluded that mathematical logical intelligence has a decisive influence on the quality of solving ratio problems at each stage of Polya.